(untitled) (Proceedings of the International Conference on Social Sciences, 2018)
In the context of institutionalized Buddhism, the position of the Buddhist monks in Sri Lankan society and the issues of their discipline have been commonly discussed and frequently debated with reference to various practices such as the involvement of monks in politics, acting militantly in public places, engaging in occult activities, and conducting trade or business activities, etc. One relatively recent event, which intensified discussions and debates on some of such activities, has been the introduction of the draft bill “The Theravada Bhikkhu Kathikawath” to the Parliament of Sri Lanka in January 2016. It marked a sudden outbreak of competing views from various segments of the lay and monastic societies on the position of Buddhist monks and the monastic reforms required on certain behavioral conducts. This study adopted a thematic analysis, which intended to explore what themes became more contentious in print and electronic media during the debate; and critically looked into how actors relevant to such contentious themes highlighted matters related to the Bill in particular and monastic reforms in general while falling into different discursive spaces. The debate uncovered several underlying problems related to the draft bill, monastic reforms and monastic community that include disagreements over the legitimacy of Mahanayakas or Chief Prelates and the lay political leadership, contradictions over the constitutionality of the draft bill; and problems over traditionalism and modernization of the Buddhist monastic community in Sri Lanka.